2022
DOI: 10.3748/wjg.v28.i40.5845
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the methylcytosine dioxygenase ten-eleven translocation-2 and connexin 43 in inflammatory bowel disease and colorectal cancer

Abstract: BACKGROUND Inflammatory bowel disease (IBD) constitutes a substantial risk factor for colorectal cancer. Connexin 43 (Cx43) is a protein that forms gap junction (GJ) complexes involved in intercellular communication, and its expression is altered under pathological conditions, such as IBD and cancer. Recent studies have implicated epigenetic processes modulating DNA methylation in the pathogenesis of diverse inflammatory and malignant diseases. The ten-eleven translocation-2 (TET-2) enzyme catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…TET proteins regulate the equilibrium between DNA methylation and demethylation by regulating the dynamic transformation among cytosine, 5-mC, and 5-hmC [ 41 ]. However, missense and truncated TET mutations have been reported in nearly all types of solid tumors [ 42 ], and their reduced protein expression and 5-hmC levels are markers of many cancer types, including colorectal cancer [ 43 ], glioblastoma [ 24 ], cervical cancer [ 44 ], and pancreatic cancer [ 45 ]. The aforementioned studies are consistent with our findings, showing that modulating the DNMT3A and TET2 expression levels could effectively change the biological behavior of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…TET proteins regulate the equilibrium between DNA methylation and demethylation by regulating the dynamic transformation among cytosine, 5-mC, and 5-hmC [ 41 ]. However, missense and truncated TET mutations have been reported in nearly all types of solid tumors [ 42 ], and their reduced protein expression and 5-hmC levels are markers of many cancer types, including colorectal cancer [ 43 ], glioblastoma [ 24 ], cervical cancer [ 44 ], and pancreatic cancer [ 45 ]. The aforementioned studies are consistent with our findings, showing that modulating the DNMT3A and TET2 expression levels could effectively change the biological behavior of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DNA methylation is counteracted by the demethylation process catalyzed by TET enzymes, which mediate a series of oxidation reactions and convert methylated 5methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), 5formylcytosine (5fC) and sequentially 5-carboxylcytosine (5caC) (Wu and Zhang, 2017). A recent study has analyzed colon tissue samples from patients with UC and CRC as well as healthy counterparts, and corroborated that the expression of TET2 and 5hmC levels decrease in those samples from patients with UC or CRC (El-Harakeh et al, 2022) (Figure 1).…”
Section: Epigenetic Modifications Dna Methylationmentioning
confidence: 96%
“…TET3 plays a crucial role in maintaining tissue homeostasis by controlling the transcriptome and DNA methylome of the gut epithelium, particularly in response to luminal stresses ( 43 ). Recent research has suggested epigenetic mechanisms modulating DNAm in the pathophysiology of various inflammatory and cancerous diseases, and the TET-2 enzyme has been shown to catalyze the demethylation, thereby controlling the activity of numerous genes that promote and repress tumors ( 44 ). Additionally, comparing normal colon tissues to those with IBD and colon cancer, the expression of TET2 and its epigenetic mark 5hmC is significantly downregulated in the latter two conditions ( 45 ).…”
Section: Enzymes and Proteins Involved In Dnam And Ibdmentioning
confidence: 99%
“…In human tissues, aberrant methylation induction is caused by DNMT activation owing to nitric oxide generation and TET inhibition due to nuclear factor κB activation ( 46 ). The expression of a protein called connexin 43 (Cx43), which is involved in gap junction complexes and intercellular communication, is altered in pathological diseases, such as cancer and IBD ( 44 ). The levels of Cx43 and the demethylating enzyme TET-2 are increased in inflammatory situations.…”
Section: Enzymes and Proteins Involved In Dnam And Ibdmentioning
confidence: 99%
See 1 more Smart Citation